Hubungan kualitas pelayanan prinsip home care dengan kepuasaan pasien perawatan luka - Anggraini, Putri; Patria, Armen; Yuliani, Eka (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The quality of home care services is an important factor in achieving patient satisfaction, especially for wound care patients. At the Mekar Arum Primary Inpatient Clinic, there is a need to assess the relationship between the quality of service provided and the level of patient satisfaction. Purpose: to analyze the relationship between the quality of home care service principles and wound care patient satisfaction at the Mekar Arum Primary Inpatient Clinic, Central Lampung, in 2024. Methods: The research method used was quantitative with a correlation design and cross sectional approach. The sample consisted of 39 respondents who were taken by total sampling. Data were collected through questionnaires measuring service quality and patient satisfaction. The results of the analysis showed that most respondents were aged 46-55 years, with the majority of female gender. The quality of service received by patients showed that 51.3% of respondents were satisfied, while 46.2% were very satisfied with the services provided. Results: The results of statistical tests obtained a significant relationship between service quality and patient satisfaction, with a P Value = 0.000 (p ≤ 0.05). Conclusion: Statistical tests using chi-square showed a p value = 0.000, which means there is a significant relationship between the quality of homecare services and patient satisfaction.   Keywords: Service Quality, Home Care, Patient Satisfaction, Wound Care.   Pendahuluan: Kualitas pelayanan home care menjadi faktor penting dalam mencapai kepuasan pasien, terutama bagi pasien perawatan luka. Di Klinik Pratama Rawat Inap Mekar Arum, terdapat kebutuhan untuk menilai hubungan antara kualitas pelayanan yang diberikan dan tingkat kepuasan pasien. Tujuan: Untuk menganalisis hubungan antara kualitas pelayanan prinsip home care dengan kepuasan pasien perawatan luka di Klinik Pratama Rawat Inap Mekar Arum, Lampung Tengah, tahun 2024. Metode: Metode penelitian yang digunakan adalah kuantitatif dengan desain korelasi dan pendekatan cross-sectional. Sampel terdiri dari 39 responden yang diambil secara total sampling. Data dikumpulkan melalui kuesioner yang mengukur kualitas pelayanan dan kepuasan pasien. Hasil analisis menunjukkan bahwa sebagian besar responden berusia 46-55 tahun, dengan mayoritas jenis kelamin perempuan. Kualitas pelayanan yang diterima pasien menunjukkan 51.3% responden merasa puas, sedangkan 46.2% menyatakan sangat puas terhadap pelayanan yang diberikan. Hasil: Hasil uji statistik diperoleh adanya hubungan yang bermakna antara kualitas pelayanan dengan kepuasaan pasien, dengan nilai P Value = 0.000 (p ≤ 0.05). Simpulan: Uji statistik menggunakan chi-square menunjukkan nilai p = 0.000, yang berarti terdapat hubungan signifikan antara kualitas pelayanan home care dengan kepuasan pasien.   Kata Kunci: Kualitas Pelayanan, Home Care, Kepuasan Pasien, Perawatan Luka